Encyclopedia of Environmental Microbiology 2003
DOI: 10.1002/0471263397.env318
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response in Archaea

Abstract: Terminology The Three Domains of Life The Beginnings Gene Cloning Discontinuous Distribution of the hsp70(dnaK) Gene within the Domain Archaea Stress Proteins in Archaea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…Hsps are an evolutionary conserved family of functionally related proteins, and many of them are molecular chaperones (Ellis, 1990;Ritossa, 1996;Walter and Buchner, 2002;Macario et al, 1999;Young et al, 2004). These are capable of recognizing and binding substrate proteins in an unstable or inactive state and assisting them in folding or refolding to achieve a native conformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsps are an evolutionary conserved family of functionally related proteins, and many of them are molecular chaperones (Ellis, 1990;Ritossa, 1996;Walter and Buchner, 2002;Macario et al, 1999;Young et al, 2004). These are capable of recognizing and binding substrate proteins in an unstable or inactive state and assisting them in folding or refolding to achieve a native conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp60, a Group I chaperonin, is found in bacteria and eukaryotic organelles, whereas Group II chaperonins occur in Archea and eukaryotic cytosol, typically forming double-ringed structures (Macario et al, 1999;. At least nine genes have been identified for Group II but only one for Group I proteins in humans (Kubota et al, 1995;Hansen et al, 2003).…”
Section: ©2008 European Journal Of Histochemistrymentioning
confidence: 99%
“…Genome sequencing projects on different methanosarcina, Methanosarcina mazei (Deppenmeier et al 2002), Methanosarcina acetivorans (Galagan et al 2002), and Methanosarcina barkeri (Maeder et al 2006), revealed that about 20-33 % of methanosarcina genes (∼1000 genes) have been acquired horizontally, including the genes encoding group I chaperonins from bacteria. These studies therefore presented the first evidence of the co-existence of group I (GroES/L) and group II (thermosome/prefoldin) chaperonin genes (Macario et al 1999(Macario et al , 2004) that are expressed concurrently (Klunker et al 2003), and distinct substrate pools (Hirtreiter et al 2009), thereby offering a fantastic model to study the evolution of chaperonin dependent protein folding. While the group II chaperonin genes that are exclusive to archaea and eukaryotes are understood to be inherited, group I chaperonin genes that are exclusive of bacterial cytosol and endosymbiotic organelle are believed to be acquired horizontally, indicating probable relationship between archaea and bacteria.…”
Section: Multiple Chaperonins In Rhizobium-the Division Of Labor Situmentioning
confidence: 99%
“…3). In archaea, the protein chaperone systems are thought to utilize DnaK, prefoldin and the thermosome to bind unfolded proteins and mediate their folding (Macario et al, 1999). The DNA repair enzymes more highly expressed in response to copper were RecA/RadA and endonuclease IV (spots 12 and 17, respectively; Table 3).…”
Section: Growth Of Fer1 In the Presence Of Cu 2+mentioning
confidence: 99%